COMPARATIVE STUDIES OF THE PHYTOCHEMICAL SCREENING AND PROXIMATE POTENTIALS OF THE METHANOLIC EXTRACTS OF CYMBOPOGON ATTRACTUS AND OCIMUM GRATISSIMUM LEAVES GROWN IN NIGERIA - Nna, Prince Joe; Joy, Nduudee N. (Acta Scientiae et Intellectus, 2024)
The phytochemical composition and proximate potentials of cymbopogon attractus and ocimum gratissimum were investigated. The proximate analysis in % showed that ocimum gratissimum had the highest amount of moisture content, ash content, crude protein and carbohydrate of 81.62, 3.03, 5.58 and 8.87 respectively while cymbopogon attractus had the lowest amount of moisture content, ash content, crude protein and carbohydrate with 76.98, 1.69, 2.87 and 8.27 respectively. Though cymbopogon attractus recorded 1.38 and 8.84 for both ether extract and crude fibre while ocimum gratissimum had 0.79 and 3.80 for ether extract and crude fibre respectively.The phytochemical analysis of the plants showed that the two plants contained alkaloid, tannins, saponins, flavonoids, phlobatanin and anthraquinone. While, cardiac glycoside,triterpenoids and reducing compound were found in cymbogopon attractus but absent in ocimum gratssimum. However, the study also revealed that steroid was present in ocimum gratissimum but absent in cymbopogon attractus while protein was not found in both plants. The presence of these phytochemicals account for their medicinal potential as well as their utility as prophylactics. This study showed the presence of steroids in ocimum gratissimum which accounts for its irritative ability in the mouth when rawly eaten while the presence of cardiac glycoside and triterpenoids in cymbopogon attractus are responsible for its sour taste.